Marija Rudzinskaitė-Arcimavičienė’s contribution to Egyptology (in commemoration of the 125th anniversary of the scholar’s birth) - Snitkuvienė, Aldona (Acta Orientalia Vilnensia, 2009)
M.K. Čiurlionis National Museum of Art The article is devoted to the contribution of Lithuania’s first professional Egyptologist, Marija Rudzinskaitė-Arcimavičienė (16 July 1885–4 May 1941), to the science of Egyptology. The discussion is centred around the formation of Rudzinskaitė-Arcimavičienė’s interest in Oriental studies, her academic activities at the University of Lithuania, her scholarly and popular publications, her scientific and organisational activities, her participation in international congresses of Orientalists, her collection of Egyptian antiquities, the most relevant trends in her scholarly research, and a general overview of her activities within the sphere of Egyptology.